Mockning som beteshygiensk åtgärd för parasitbekämpning hos häst - Thorolfson Rainamo, Helena (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2018)
A field study of the effect of faecal removal from pasture on prevalence of equine parasites Strongylus vulgaris (S. vulgaris) is one of the most pathogenic parasites in horses. To control S. vulgaris, chemical substances named anthelmintics were introduced in the 1960`s.These drugs were used in what was called interval dose systems where horses were treated at two month intervals year round. This led to a decline of S. vulgaris and an increase of cyathostomins, resistant to all three available classes of anthelmintics. Today cyathostomins are the most prevalent parasites affecting horses. The cyathostomins can be pathogenic. Since the 90`s no new anthelmintic classes have been introduced and there is a substantial risk that anthelmintics used today no longer will be effective in the future. Resistant cyathostomins are now a threat to equine welfare and therefore research to develop non-chemical alternatives for parasite control is needed. Infectious third stage larvae, L3, are ingested by horses on pastures. One alternative method includes manual faecal removal from pasture where little work has been done to confirm the effectiveness of this method. The aim of this study was to elucidate if manual faecal removal from pasture twice a week can reduce the amount of infectious larvae found in grass samples from pasture. The hypothesis was that the average larval counts from the pasture were faeces was removed manually twice a week would be lower than the average larval counts from the pasture were faeces was not remowed. In this study, grass samples were collected from two pastures, where three horses with known egg shedding were grazing. Every other day, the horses were transfered from one pasture to the other. From one of the pastures, faeces were removed manually, twice a week. From the other pasture, no faeces were removed. Samples were preparated in the laboratory and L3-larvae were counted under a microscope. The L3-larval counts from the pasture where faeces were removed manually twice a week, resulted in an average number of seven compared to the larval counts obtained from the pasture from which there was no faecal removal where the average number was 3480. This indicates that removing equine faeces from pasture twice a week could be an effective method to reduce infectious L3-larvae in the grass and help to control parasite infection.